Nuclear Factor κB-COX2 Pathway Activation in Non-myelinating Schwann Cells Is Necessary for the Maintenance of Neuropathic Pain in vivo - Xie, Alison Xiaoqiao; Taves, Sarah; McCarthy, Ken (Frontiers in Cellular Neuroscience, 2022)
Chronic neuropathic pain leads to long-term changes in the sensitivity of both peripheral and central nociceptive neurons. Glial fibrillary acidic protein (GFAP)-positive glial cells are closely associated with the nociceptive neurons including astrocytes in the central nervous system (CNS), satellite glial cells (SGCs) in the sensory ganglia, and non-myelinating Schwann cells (NMSCs) in the peripheral nerves. Central and peripheral GFAP-positive cells are involved in the maintenance of chronic pain through a host of inflammatory cytokines, many of which are under control of the transcription factor nuclear factor κB (NFκB) and the enzyme cyclooxygenase 2 (COX2). To test the hypothesis that inhibiting GFAP-positive glial signaling alleviates chronic pain, we used (1) a conditional knockout (cKO) mouse expressing Cre recombinase under the hGFAP promoter and a floxed COX2 gene to inactivate the COX2 gene specifically in GFAP-positive cells; and (2) a tet-Off tetracycline transactivator system to suppress NFκB activation in GFAP-positive cells. We found that neuropathic pain behavior following spared nerve injury (SNI) significantly decreased in COX2 cKO mice as well as in mice with decreased glial NFκB signaling. Additionally, experiments were performed to determine whether central or peripheral glial NFκB signaling contributes to the maintenance of chronic pain behavior following nerve injury. Oxytetracycline (Oxy), a blood-brain barrier impermeable analog of doxycycline was employed to restrict transgene expression to CNS glia only, leaving peripheral glial signaling intact. Signaling inactivation in central GFAP-positive glia alone failed to exhibit the same analgesic effects as previously observed in animals with both central and peripheral glial signaling inhibition. These data suggest that the NFκB-COX2 signaling pathway in NMSCs is necessary for the maintenance of neuropathic pain in vivo.